An Empirical Analysis of Credibility Assessment in German Asylum Cases - Baade, Björnstjern; Gölz, Leah (German law journal, 2023)
This study analyzes empirically how 236 German court decisions assess the credibility of asylum seekers’ accounts of their persecution. In their reasoning, the courts rely on generally accepted content-based credibility criteria, including consistency, level of detail, and timeliness of the claim. But they also rely on conduct-based criteria, which have been resoundingly discredited in the relevant scientific literature. Too rarely, the courts considered confounding factors such as cultural distance or interpreter mistakes. They need to be more aware of their duty to confront applicants with negative credibility criteria. Article 4 (5) Qualification Directive played no role whatsoever in the sample analyzed in this study, which can be explained by specifics of German asylum law. The human judgment that is required in the balancing of credibility criteria and confounding factors is problematic for its subjectivity but unavoidable. Attempts at replacing this human credibility assessment with seemingly objective technical means have led to arbitrary decisions and encroached gravely on applicants’ human rights. While the credibility assessment procedure employed in German courts is far from flawless, it can produce convincing decisions. It should be further refined and provided with safeguards to arrive at decisions that are as rational and objective as possible.